2016
DOI: 10.1007/s00114-016-1378-8
|View full text |Cite
|
Sign up to set email alerts
|

A structural colour ornament correlates positively with parasite load and body condition in an insular lizard species

Abstract: Pigment-based ornaments in vertebrates may reflect the body condition or health status of the individual in correlation with environmental stress and hormonal balance. Among the environmental factors shaping sexual colouration, parasitic infections have been stressed as an important evolutionary pressure constraining the maintenance of pigment-based ornaments. However, the honesty of structure-based ornaments in vertebrates is still under debate. Structural UV-biased ornaments in Gallotia lizards were describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 77 publications
3
36
1
2
Order By: Relevance
“…Parasite prevalence, parasitaemia and genetic diversity were higher in Gallotia hosts than in Tarentola and Chalcides (values in Gallotia spp. were consistent with previous studies [ 39 43 ]). Interestingly, a similar trend was also observed in nematodes of the genus Spauligodon infecting the same hosts [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Parasite prevalence, parasitaemia and genetic diversity were higher in Gallotia hosts than in Tarentola and Chalcides (values in Gallotia spp. were consistent with previous studies [ 39 43 ]). Interestingly, a similar trend was also observed in nematodes of the genus Spauligodon infecting the same hosts [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, this widening of host breadth seems to have been temporary, as contemporary host-parasite associations show a high level of host specificity, differing from the Island Syndrome expectations. Regarding haemogregarines, these parasites have been found in the archipelago infecting lizards of the genera Gallotia [ 38 – 43 ] and Tarentola [ 44 ]. However, in most cases detection was based on microscopy, and only one work suggests different haemogregarine morphological forms infecting Gallotia [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…2013 ), which is not consistent with the pattern of hemoparasite variation reported here. Lizards could be more susceptible to hemoparasites at high elevations, given that highland lizards invest more resources in colour signals ( Reguera 2015 ), and other studies have reported that lizards with more colorful colorations suffer from increased infection by hemoparasites ( Megía-Palma et al. 2016a , 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed thin blood smears that were air dried and fixed with methanol. Smears were stained for 40 min with Giemsa diluted 1: 10 in buffer, pH 7.2 ( Megía-Palma et al. 2016a , 2016b ).…”
Section: Methodsmentioning
confidence: 99%
“…Well‐fed lizards were also able to maintain more intense throat coloration than food‐deprived individuals. Production and maintenance of structural colors have been shown to be energetically costly (Megía‐Palma, Martínez, & Merino, ; Prum, ), with both developmental stress and available nutrients influencing coloration in lizards (Olsson et al., ). Additionally, previous studies showed that nuptial throat coloration is condition dependent (Molnár et al., ) and affected by environmental factors (Bajer et al., ) in the study species.…”
Section: Discussionmentioning
confidence: 99%